2022
DOI: 10.3389/fphys.2022.1007418
|View full text |Cite
|
Sign up to set email alerts
|

Modelling premature cardiac aging with induced pluripotent stem cells from a hutchinson-gilford Progeria Syndrome patient

Abstract: Hutchinson-Gilford Progeria Syndrome (HGPS) is a rare genetic disorder that causes accelerated aging and a high risk of cardiovascular complications. However, the underlying mechanisms of cardiac complications of this syndrome are not fully understood. This study modeled HGPS using cardiomyocytes (CM) derived from induced pluripotent stem cells (iPSC) derived from a patient with HGPS and characterized the biophysical, morphological, and molecular changes found in these CM compared to CM derived from a healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Interestingly, a recent study using induced pluripotent stem cell-derived cardiomyocytes from a patient with Hutchinson–Gilford Progeria Syndrome found that premature aging is also associated with mitochondrial alterations in cardiac cells. The study discovered structural abnormalities in mitochondria, while high-resolution proteomics data revealed significant changes in protein expression related to the tricarboxylic acid cycle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study using induced pluripotent stem cell-derived cardiomyocytes from a patient with Hutchinson–Gilford Progeria Syndrome found that premature aging is also associated with mitochondrial alterations in cardiac cells. The study discovered structural abnormalities in mitochondria, while high-resolution proteomics data revealed significant changes in protein expression related to the tricarboxylic acid cycle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This potential utility of iPSCs in aging research has recently been highlighted as a platform for both longevity studies as well as drug discovery 23 . EL iPSCs also provide a complement for studies performed on aging disease-specific lines, such as those derived from patients with Progeria 24,25 , given their potential in understanding mechanisms that embolden resiliency and resistance to accelerated aging-related disease.…”
Section: Introductionmentioning
confidence: 99%
“…disease-specific lines, such as those derived from patients with Progeria 24,25 , given their potential in understanding mechanisms that embolden resiliency and resistance to accelerated aging-related disease. Here, we report a novel bank of longevity-specific peripheral blood mononuclear cells (PBMCs) and resultant iPSCs from subjects with EL.…”
mentioning
confidence: 99%